Cognitive Radio Based Optimal Channel Sensing for Resource Allocation in Communications - Morshed, M. N.; Khatun, S.; Vijayasarveswari, V.; Fakir, M. M.; Ibrahim, M. Z.; Hawari, K.; Ariff, M. H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Cognitive Radio (CR) is the cutting-edge wireless technology that is used to solve the spectrum saturation problem. In cognitive radio, Secondary Users (SUs) use Primary User’s (PU’s) spectrum (licensed band) during PU’s absence. Cognitive radio provides more flexibility in terms of spectrum utilization but the spectrum sensing efficiency need to be improved to make sure that the PUs are not interrupted while they are active. This paper presents the test-bed development of a CR network using Android-based smartphones for optimal sensing and data transmission. An energy detector based sensing method is proposed and used here since the energy detector does not require the information of the PU. The CR features have been implemented in Android phone using the Eclipse Java programming. The test-bed experimental set up was done using Android-based smartphones and Wi-Fi Access Point (AP). Two spectrum, Wi-Fi and Bluetooth were used to verify the sensing and detection efficiency. Results show that the proposed sensing and detection scheme efficiency is about 83%.